Monolithic catalyst, preparation method and application thereof, and method for synergistically purifying carbon monoxide and volatile organic compounds

By using a monolithic catalyst with a porous matrix loaded with manganese oxide and a protective agent, the problems of complexity and high cost of CO and VOCs purification methods in the prior art are solved, efficient and stable synergistic purification effects are achieved, and the preparation and use costs are reduced.

CN119909671AActive Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311432307.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02
Estimated Expiration
2043-10-31

AI Technical Summary

Technical Problem

In the purification of CO and VOCs, existing catalysts have problems such as complex preparation methods, high cost and failure to effectively coordinate purification.

Method used

A monolithic catalyst with a porous matrix loaded with manganese oxide and a protective agent was prepared by impregnation method and applied in exhaust gas treatment to coordinate the purification of carbon monoxide and volatile organic matter.

Benefits of technology

It achieves efficient and stable CO and VOCs removal, reduces preparation costs, simplifies the process flow, and extends the service life of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of air pollution control, and discloses a monolithic catalyst, a preparation method and application thereof, and a method for synergistically purifying carbon monoxide and volatile organic compounds. The monolithic catalyst comprises a porous substrate, manganese oxide and a protective agent, the manganese oxide and the protective agent are loaded on the porous substrate, and the protective agent is selected from at least one of an acidic substance, an alkaline substance and a metal oxide; wherein the average valence of manganese in the monolithic catalyst is 3.6 to 4. The monolithic catalyst has excellent oxidation capacity, is applied to synergistic purification of carbon monoxide and volatile organic compounds, and has the advantage of good removal effect of carbon monoxide and volatile organic compounds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of air pollution control, and in particular to an integral catalyst, a preparation method and application thereof, and a method for synergistically purifying carbon monoxide and volatile organic compounds. Background Art

[0002] Volatile organic compounds (VOCs) are a class of volatile organic compounds with boiling points between 50-260°C. They are highly toxic and polluting chemicals. Many VOCs can cause lesions in the human body and even cause cancer. Under light irradiation, VOCs generate photochemical smog, and some halogenated hydrocarbons can cause ozone layer destruction. In view of the catastrophic harm that VOCs pollution brings to the earth's environment and human health, seeking effective governance technologies has become the only way to solve VOCs pollution. The exhaust gas from industries such as steel sintering and waste incineration and the exhaust gas from motor vehicles contain a large amount of pollutants such as particulate matter, SO2, NO x For example, in the steel industry, the Ministry of Environmental Protection issued the "Emission Standards for Air Pollutants from Steel Sintering and Pelletizing Industries" (GB28662-2012) in 2012. The main pollutants produced by sintering equipment are 50mg / m 3 、SO2 200mg / m 3 、NO x 300 mg / m 3 , CO 5000mg / m 3 Among them, CO is a reducing gas widely present in steel sintering, waste incineration flue gas and automobile exhaust. NO in the atmosphere x The interaction between sulfur oxides and VOCs causes primary particulate matter in the atmosphere to transform into secondary particulate matter pollutants, which in turn leads to smog weather. Therefore, controlling the emission of VOCs and CO is of great significance to improving the air quality in my country.

[0003] CN107519871A discloses a method for preparing a AuAg@SiO2 nanocatalyst for catalytic oxidation of CO, wherein the method comprises the following specific steps: (1) mixing a 10 mM HAuCl4 solution and a 10 mM AgNO3 solution, adding a 0.1 g / ml surfactant solution, stirring at room temperature for 20-30 min, adding a 0.1 M sodium borohydride solution, stirring for 3 h, and obtaining an AuAg alloy sol; the 10 mM The volume ratio of HAuCl4 solution, 10mMAgNO3 solution, 0.1g / ml surfactant and 0.1M sodium borohydride is 1:0.25-4:0.5-10:1-10; (2) taking the AuAg alloy sol obtained in step (1), adding a solvent, adding tetraethyl orthosilicate (TEOS) under stirring, adding 28wt% ammonia water dropwise after mixing evenly, and continuing to stir for 2-5 hours; wherein the solvent is a mixture of water and alcohol, and the volume ratio of water to alcohol is 1:1.25-5; the volume ratio of AuAg alloy sol, tetraethyl orthosilicate and 28wt% ammonia water is 1:0.05-0.3:0.1-1. The above scheme has the problems of complex catalyst preparation method and high preparation cost.

[0004] CN103263917A discloses a method for preparing a Pt-BaTiO3 nanocatalyst for CO catalytic oxidation, which adopts a wet chemical reaction method, using tetragonal perovskite BaTiO3 nanoparticles synthesized by a hydrothermal method, H2PtCl6·6H2O, NaBH4 and deionized water as reaction materials, using the reducing property of NaBH4 to reduce Pt to the surface of BaTiO3 nanoparticles to form unstable Pt nanoparticles, and then making it completely crystallized on the surface of BaTiO3 ferroelectric nanoparticles in a subsequent drying process, thereby obtaining a Pt-BaTiO3 nanocatalyst for CO catalytic oxidation. However, the CO purification catalyst provided by the above method is not suitable for large-scale use due to the poor economy of using the precious metal Pt, the complex preparation method and the harsh reaction conditions.

[0005] In the field of air pollution control, although the above catalysts can improve the purification capacity of CO and VOCs to a certain extent, there is still room for further improvement, and previous patents and literature have not studied the synergistic purification of VOCs and CO by catalysts. Therefore, it is of great practical significance to develop a catalytic oxidation catalyst that can remove CO and VOCs at the same time. Summary of the invention

[0006] The purpose of the present invention is to overcome the problems existing in the prior art and provide a monolithic catalyst and its preparation method and application as well as a method for synergistically purifying carbon monoxide and volatile organic compounds. The monolithic catalyst has excellent oxidation ability and is applied to synergistically purifying carbon monoxide and volatile organic compounds, and has the advantage of good removal effect of carbon monoxide and volatile organic compounds.

[0007] In order to achieve the above object, the first aspect of the present invention provides a monolithic catalyst, the catalyst comprising a porous substrate and manganese oxide and a protective agent supported on the porous substrate, the protective agent being selected from at least one of an acidic substance, an alkaline substance and a metal oxide;

[0008] Wherein, the average valence of manganese in the monolithic catalyst is 3.6-4.

[0009] A second aspect of the present invention provides a method for preparing a monolithic catalyst, the method comprising the following steps:

[0010] (1) mixing a manganese-based material with a dispersant and a binder to obtain a manganese oxide suspension, wherein the average valence of manganese in the manganese-based material is 3.6-4;

[0011] (2) impregnating the porous substrate into a suspension of manganese oxide and a suspension of a protective agent by an impregnation method, followed by drying and optional calcination;

[0012] Wherein, the protective agent is selected from at least one of an acidic substance, an alkaline substance and a metal oxide.

[0013] The third aspect of the present invention provides an application of the integral catalyst described in the first aspect or the integral catalyst prepared by the preparation method described in the second aspect in exhaust gas treatment, preferably in the coordinated purification of carbon monoxide and volatile organic compounds.

[0014] A fourth aspect of the present invention provides a method for synergistically purifying carbon monoxide and volatile organic compounds, the method comprising: contacting tail gas containing carbon monoxide and volatile organic compounds with an integral catalyst;

[0015] Wherein, the monolithic catalyst is the monolithic catalyst described in the first aspect or the monolithic catalyst prepared by the preparation method described in the second aspect.

[0016] Through the above technical solution, the beneficial effects of the present invention include:

[0017] The porous matrix, manganese oxide and protective agent in the monolithic catalyst provided by the present invention play a synergistic role, and the average valence of manganese in the monolithic catalyst is regulated to be 3.6-4, so that the catalyst has excellent oxidation ability. The catalyst is applied to the coordinated purification of carbon monoxide and volatile organic compounds, and can efficiently and stably remove carbon monoxide and volatile organic compounds (VOCs), meeting the atmospheric requirements for the concentration of carbon monoxide and volatile organic compounds.

[0018] The monolithic catalyst provided by the present invention has a simple preparation process, low cost and high decarbonization accuracy, and is conducive to industrial promotion. DETAILED DESCRIPTION

[0019] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0020] The first aspect of the present invention provides a monolithic catalyst, the catalyst comprising a porous substrate, and manganese oxide and a protective agent supported on the porous substrate, wherein the protective agent is selected from at least one of an acidic substance, an alkaline substance and a metal oxide;

[0021] Wherein, the average valence of manganese in the monolithic catalyst is 3.6-4.

[0022] The inventors of the present invention have discovered that the monolithic catalyst uses a porous matrix-manganese oxide-protective agent to exert a synergistic effect, utilizing the adsorption capacity and catalytic oxidation capacity of manganese oxide, the impurity removal capacity of the protective agent and the stability of the porous matrix, and in the application of synergistic purification of carbon monoxide and volatile organic compounds, can achieve the purpose of efficiently and stably eliminating volatile organic pollutants such as CO and volatile organic compounds (VOCs).

[0023] In the present invention, the average valence of manganese in the monolithic catalyst is 3.6-4. Controlling the average valence of manganese in the monolithic catalyst at a relatively high level is conducive to the thorough oxidation of CO and VOCs, and achieving the coordinated purification of carbon monoxide and volatile organic compounds.

[0024] The average valence AOS of manganese in the present invention is calculated by the following calculation formula:

[0025] AOS = 8.956-1.126×ΔE, ΔE is the difference between the high binding energy and the low binding energy of manganese measured by XPS Mn3S.

[0026] According to the present invention, preferably, based on the total weight of the monolithic catalyst, in the monolithic catalyst, the content of the porous matrix is ​​50-80% by weight, preferably 55-80% by weight; the content of manganese oxide is 10-40% by weight, preferably 15-35% by weight; the content of the protective agent is 5-35% by weight, preferably 5-30% by weight. This preferred embodiment is conducive to improving the oxidation capacity of the monolithic catalyst and protecting the active phase of the catalyst from being poisoned by the poisonous gas in the tail gas, thereby extending the service life of the catalyst.

[0027] The content of each component in the monolithic catalyst of the present invention is calculated by the feed amount.

[0028] Preferably, the monolithic catalyst further contains a binder. In the monolithic catalyst of the present invention, the balance is the binder.

[0029] The present invention has no particular limitation on the type of the binder, which can be selected conventionally in the art and will not be described in detail herein.

[0030] The sum of the components in the catalyst of the present invention is 100%.

[0031] The monolithic catalyst of the present invention has a special active phase crystal structure, which is beneficial to improving the conversion efficiency of CO and VOCs. Preferably, the manganese oxide has an α-MnO2 structure.

[0032] The crystal structure of the manganese oxide described in the present invention is obtained by XRD measurement.

[0033] The protective agent in the monolithic catalyst of the present invention has a strong ability to remove impurities and can be contacted with tail gas first, which is beneficial to protect the active phase of the catalyst from being poisoned by poisonous gases in the tail gas and prolong the service life of the catalyst.

[0034] According to the present invention, preferably, the protective agent is selected from at least two of an acidic substance, an alkaline substance and a metal oxide.

[0035] According to the present invention, preferably, the protective agent is a metal oxide, and an alkaline substance and / or an acidic substance. The use of the above-mentioned multiple protective agents synergistically is more conducive to improving the long-term use effect of the catalyst.

[0036] According to the present invention, preferably, the mass ratio of the metal oxide to the alkaline substance and / or the acidic substance is 1: 1-8, preferably 1: 1-4. This preferred embodiment is further conducive to improving the long-term use effect of the catalyst.

[0037] Preferably, the acidic substance is selected from at least one of ethyl titanate, isopropyl titanate, tetrabutyl titanate, tetraethyl silicate, ethyl orthosilicate, methyl orthosilicate and ethyl methyl silicate, more preferably tetrabutyl titanate and / or ethyl orthosilicate.

[0038] Preferably, the alkaline substance is an inorganic base, preferably at least one selected from sodium carbonate, potassium carbonate, sodium hydroxide and potassium hydroxide.

[0039] Preferably, the metal oxide is zinc oxide and / or iron oxide.

[0040] The use of the above-mentioned specific types of protective agents is beneficial to improving the long-term use effect of the catalyst.

[0041] In the present invention, the structure (structural type) of the porous matrix can be at least one of a particle stacking type, a straight hole grid type, a fiber grid type and a foam type, and is preferably a honeycomb carrier.

[0042] The present invention has no particular limitation on the type of the honeycomb support, which can be a conventional choice in the art. Preferably, the porous matrix is ​​selected from at least one of a cordierite honeycomb support, a mullite honeycomb support, a diamond honeycomb support, a corundum honeycomb support, a zirconium corundum honeycomb support, a quartz honeycomb support, a nepheline honeycomb support, a feldspar honeycomb support, an alumina honeycomb support and a metal alloy honeycomb support, and more preferably a cordierite honeycomb support.

[0043] A second aspect of the present invention provides a method for preparing a monolithic catalyst, the method comprising the following steps:

[0044] (1) mixing a manganese-based material with a dispersant and a binder to obtain a manganese oxide suspension, wherein the average valence of manganese in the manganese-based material is 3.6-4;

[0045] (2) impregnating the porous substrate into a suspension of manganese oxide and a suspension of a protective agent by an impregnation method, followed by drying and optional calcination;

[0046] Wherein, the protective agent is selected from at least one of an acidic substance, an alkaline substance and a metal oxide.

[0047] According to the present invention, preferably, the amount of manganese-based material, protective agent and porous matrix is ​​such that in the prepared monolithic catalyst, based on the total weight of the monolithic catalyst, the content of the porous matrix is ​​50-80% by weight, preferably 55-80% by weight; the content of manganese oxide is 10-40% by weight, preferably 15-35% by weight; the content of the protective agent is 5-35% by weight, preferably 5-30% by weight.

[0048] According to the present invention, preferably, in the manganese oxide suspension, D of the manganese-based material 90The thickness of the coating layer is not greater than 10 micrometers, preferably 1-5 micrometers. With this preferred embodiment, it is easier to form a stable coating layer.

[0049] The present invention has no particular limitation on how to obtain the average particle size of the manganese-based material within the above range, and it can be achieved by conventional technical means, such as grinding.

[0050] According to the present invention, preferably, the mass ratio of the manganese-based material to the dispersant and the binder on a dry basis is 1:0.05-0.7:0.05-0.8, preferably 1:0.1-0.4:0.1-0.4.

[0051] The present invention has a wide range of selection for the type of the dispersant. Preferably, the dispersant is selected from at least one of polyvinyl alcohol, acrylic acid and methyl acrylate.

[0052] The present invention has a wide range of choices for the type of the binder, and can be various binders commonly used in the art. Preferably, the binder is selected from at least one of silica sol, alumina sol, pseudo-boehmite and phosphate aluminum sol.

[0053] According to the present invention, preferably, the manganese oxide suspension further contains water, and the amount of water used is 30-200 g relative to 1 g of manganese-based material.

[0054] According to the present invention, preferably, the manganese oxide suspension does not contain a surfactant. The surfactant can be a conventional choice in the art, and the present invention will not be described in detail here.

[0055] According to a specific embodiment of the present invention, step (1) comprises: mixing the manganese-based material with a dispersant and a binder, and then grinding for 1-3 hours to obtain a uniformly mixed manganese oxide suspension.

[0056] According to the present invention, preferably, the method for preparing the manganese-based material comprises the following steps: precipitating the first manganese-containing compound aqueous solution and the second manganese-containing compound aqueous solution, and then crystallizing to obtain the manganese-based material.

[0057] According to the present invention, preferably, the conditions of the precipitation reaction include: temperature of 30-90° C. and time of 0.3-3 h.

[0058] According to the present invention, preferably, the crystallization conditions include: temperature of 100-150° C. and time of 1-20 h.

[0059] Preferably, the method further comprises: filtering and washing the crystallized product to obtain a manganese-based material.

[0060] The present invention has no particular limitation on the specific methods of filtering and washing, and the filtering and washing can be performed according to conventional methods in the art.

[0061] The present invention has no particular limitation on the number of washing times, and the pH value of the washing agent used for washing is 7.

[0062] According to the present invention, preferably, the first manganese-containing compound is potassium permanganate and / or sodium permanganate.

[0063] According to the present invention, preferably, the second manganese-containing compound is selected from at least one of manganese sulfate, manganese nitrate and manganese acetate.

[0064] In the present invention, the average valence of manganese in the manganese-based material is regulated by reacting a first manganese-containing compound containing high-valent manganese with a second manganese-containing compound containing low-valent manganese.

[0065] According to the present invention, preferably, the concentration of the first manganese compound-containing aqueous solution is 2-15 wt %.

[0066] According to the present invention, preferably, the concentration of the second manganese compound-containing aqueous solution is 30-70 wt %.

[0067] During the preparation of the first manganese compound-containing aqueous solution and the second manganese compound-containing aqueous solution, ultrasound or stirring may be used to mix them uniformly. The same is true for the preparation of the following solutions.

[0068] The present invention has no particular limitation on the amount of the first manganese-containing compound and the second manganese-containing compound, provided that the average valence of manganese in the manganese-based material is within the above range.

[0069] According to the present invention, preferably, the impregnation method in step (2) comprises: contacting the porous substrate with a manganese oxide suspension, followed by drying and calcining to obtain a solid product; contacting the solid product with a protective agent suspension, followed by drying.

[0070] The present invention does not have any particular limitation on the contact temperature of step (2), which can be any temperature that the impregnation liquid can reach. There is no particular limitation on the contact time, as long as the required amount of metal precursor can be loaded on the carrier. In general, the higher the contact temperature and the greater the concentration of the impregnation liquid, the shorter the time required to achieve the same impregnation amount (i.e., the weight difference between the carrier after impregnation and before impregnation); and vice versa. Once the required impregnation amount and conditions are determined, it is easy to select a suitable contact time. The specific operation of the impregnation method is well known to those skilled in the art, and the impregnation method can be a saturated impregnation method or a supersaturated impregnation method. There is no particular limitation on the environment of the impregnation method, and it can be carried out under sealed conditions or in an open environment according to conventional methods in the art, and the lost solvent can be replenished during the contact process or not. Various gases, such as air, nitrogen, water vapor, etc., can be introduced during the contact process, or no new components can be introduced.

[0071] The present invention has no particular limitation on the specific conditions of the drying, and the drying can be carried out according to conventional methods in the art. Preferably, the drying conditions include: a temperature of 80-120° C. and a time of 1-5 hours.

[0072] According to the present invention, preferably, the calcination conditions include: a temperature of 300-500° C. and a time of 1-5 hours. This preferred embodiment is beneficial to improving the oxidation capacity of the catalyst.

[0073] Preferably, the protective agent is selected from at least two of an acidic substance, an alkaline substance and a metal oxide.

[0074] More preferably, the protective agent is a metal oxide, and an alkaline substance and / or an acidic substance.

[0075] According to the present invention, preferably, the mass ratio of the metal oxide to the alkaline substance and / or the acidic substance is 1:1-8, preferably 1:1-4.

[0076] Preferably, the acidic substance is selected from at least one of ethyl titanate, isopropyl titanate, tetrabutyl titanate, tetraethyl silicate, ethyl orthosilicate, methyl orthosilicate and ethyl methyl silicate, more preferably tetrabutyl titanate and / or ethyl orthosilicate.

[0077] Preferably, the alkaline substance is an inorganic base, preferably at least one selected from sodium carbonate, potassium carbonate, sodium hydroxide and potassium hydroxide.

[0078] Preferably, the metal oxide is zinc oxide and / or iron oxide.

[0079] Preferably, in the protective agent suspension, the protective agent has a D 90 The thickness is not greater than 10 micrometers, preferably 1-10 micrometers. With this preferred embodiment, the coating layer can be effectively contacted with manganese oxide, and a uniform and stable coating layer can be formed more easily.

[0080] The present invention has no particular limitation on how to obtain the average particle size of the protective agent within the above range, and it can be achieved by conventional technical means, such as grinding.

[0081] According to the present invention, preferably, the concentration of the protective agent suspension is 50-250 g / L.

[0082] Preferably, the protective agent is dissolved in water to obtain an activated carbon suspension.

[0083] In the present invention, the structure (structural type) of the porous matrix can be at least one of a particle stacking type, a straight hole grid type, a fiber grid type and a foam type, and is preferably a honeycomb carrier.

[0084] The present invention has no particular limitation on the type of the honeycomb support, which can be a conventional choice in the art. Preferably, the porous matrix is ​​selected from at least one of a cordierite honeycomb support, a mullite honeycomb support, a diamond honeycomb support, a corundum honeycomb support, a zirconium corundum honeycomb support, a quartz honeycomb support, a nepheline honeycomb support, a feldspar honeycomb support, an alumina honeycomb support and a metal alloy honeycomb support, and more preferably a cordierite honeycomb support.

[0085] The present invention has no particular limitation on the size of the porous substrate, which can be appropriately selected according to different application sites.

[0086] According to the present invention, preferably, the method further comprises: activating the material obtained in step (2) to obtain a monolithic catalyst.

[0087] According to the present invention, preferably, the activation conditions include: an activation temperature of 50-350° C., preferably 100-300° C.; and an activation time of 0.5-5 hours, preferably 0.8-3 hours.

[0088] Preferably, the activation is carried out in the presence of an activation gas, the activation gas comprises oxygen and an inert gas, and the volume content of the inert gas in the activation gas is 1-50%, preferably 2-30%.

[0089] Preferably, the inert gas is selected from at least one of nitrogen, helium, neon and argon, preferably nitrogen.

[0090] The use of the above-mentioned specific activation method is beneficial to improving the reaction conversion rate.

[0091] The third aspect of the present invention provides an application of the integral catalyst described in the first aspect or the integral catalyst prepared by the preparation method described in the second aspect in waste gas treatment, preferably in the coordinated purification of carbon monoxide and volatile organic compounds, and more preferably in the coordinated purification of carbon monoxide and volatile organic compounds in at least one of refinery exhaust gas, power plant exhaust gas, steel mill exhaust gas, flue gas generated by urban waste incineration and motor vehicle exhaust gas.

[0092] The fourth aspect of the present invention provides a method for synergistically purifying carbon monoxide and volatile organic compounds, the method comprising: contacting exhaust gas containing carbon monoxide and volatile organic compounds with an integral catalyst; wherein the integral catalyst is the integral catalyst described in the first aspect or the integral catalyst prepared by the preparation method described in the second aspect.

[0093] Preferably, the contact conditions include: temperature of 20-500°C, preferably 100-400°C; volume space velocity of 500-100000h -1 , preferably 2000-20000h -1 .

[0094] The monolithic catalyst of the present invention can be applied to treating carbon monoxide and volatile organic compounds of different concentrations.

[0095] Preferably, the carbon monoxide content in the tail gas is 0.1-5000 ppm.

[0096] According to the present invention, preferably, the content of volatile organic matter in the tail gas is 10-300 ppm.

[0097] The monolithic catalyst of the present invention can be applied to the treatment of different types of tail gas. Preferably, the tail gas includes at least one of tail gas from refineries, tail gas from power plants, tail gas from steel mills, flue gas from urban waste incineration, and tail gas from motor vehicles. The tail gas contains a lot of poisonous gases, such as SO2, NO2, NH3, etc., which have a great poisoning effect on the catalyst. The monolithic catalyst provided by the present invention not only has the advantage of good removal effect of carbon monoxide and volatile organic compounds, but also can greatly inhibit the poisoning effect of poisons and prolong the service life of the catalyst.

[0098] In the present invention, the "first" and "second" do not limit the substances and operations, but are only used to distinguish the substances introduced in different steps and the operations performed in different stages.

[0099] The present invention will be described in detail below through examples.

[0100] The concentrations of carbon monoxide, sulfur dioxide and volatile organic compounds in the exhaust gas were measured by gas chromatography.

[0101] Example 1

[0102] Preparation of manganese oxide suspension: 4.17g potassium permanganate was dissolved in 40.55g deionized water, heated to 60°C and stirred to dissolve to form a potassium permanganate solution, which was mixed with 5.78g of 50 wt% manganese sulfate solution for 3h, and then reacted at 130°C for 18h. The generated brown precipitate was filtered and washed with deionized water for several times until the pH of the washing solution was 7. The filter cake obtained was a manganese-based material. The average valence of manganese in the manganese-based material was 3.88. The manganese-based material was ground to D using a ball mill. 90 The particle size was 4 microns, and then polyvinyl alcohol (Shanghai Petrochemical): silica sol (15 wt% SiO2) on a dry basis: manganese-based material: water were added in a mass ratio of 1:1:10:88, and the ball mill was continued to grind for 2 hours to obtain a manganese oxide suspension.

[0103] Impregnation of manganese oxide suspension: The cordierite substrate was impregnated in the manganese oxide suspension for 2 minutes, then dried at 80° C. for 3 hours, and calcined at 350° C. for 2 hours to obtain a solid product.

[0104] Impregnation protective agent suspension: put zinc oxide and sodium carbonate in water at a mass ratio of 1:1, and grind them to D 90 = 8 microns, and a protective agent suspension with a concentration of 200 g / L is obtained. The solid product is immersed in the protective agent suspension for 2 minutes, dried at 120°C for 3 hours, and then activated: the activation temperature is 350°C; the activation time is 4 hours, and the activation gas includes 5% volume % oxygen and 95% volume % nitrogen.

[0105] The monolithic catalyst A1 is obtained. The composition and characteristics of the monolithic catalyst are shown in Table 1.

[0106] Example 2

[0107] Preparation of manganese oxide suspension: 3.88g potassium permanganate is dissolved in 40.55g deionized water, heated to 60°C and stirred to dissolve to form a potassium permanganate solution, which is mixed with 5.78g of a 50 wt% manganese sulfate aqueous solution for 3h, and then reacted at 130°C for 18h, and the generated brown precipitate is filtered and washed with deionized water for multiple times until the pH of the washing solution is 7, and the filter cake obtained is a manganese-based material. Among them, the average valence of manganese in the manganese-based material is 3.88.

[0108] The manganese-based material is ground to D using a ball mill. 90 The particle size was 5 microns, and then polyvinyl alcohol (Shanghai Petrochemical): silica sol (15 wt% SiO2) on a dry basis: manganese-based material: water were added in a mass ratio of 1:1:8:90, and the ball mill was continued to grind for 2 hours to obtain a manganese oxide suspension.

[0109] Impregnation of manganese oxide suspension: The cordierite substrate was impregnated in the manganese oxide suspension for 2 minutes, then dried at 80° C. for 3 hours, and calcined at 350° C. for 2 hours to obtain a solid product.

[0110] Impregnation protective agent suspension: put zinc oxide and sodium carbonate in water at a mass ratio of 1:3, and grind them to D using a ball mill. 90 =6 microns, and a protective agent suspension with a concentration of 200 g / L is obtained. The solid product is immersed in the protective agent suspension for 2 minutes, dried at 120°C for 3 hours, and then activated: the activation temperature is 450°C; the activation time is 3 hours, and the activation gas includes 3 volume % oxygen and 97 volume % nitrogen.

[0111] The monolithic catalyst A2 is obtained. The composition and characteristics of the monolithic catalyst are shown in Table 1.

[0112] Example 3

[0113] Preparation of manganese oxide suspension: 3.64g potassium permanganate was dissolved in 40.55g deionized water, heated to 60°C and stirred to dissolve to form a potassium permanganate solution, which was mixed with 5.78g of a 50 wt% manganese sulfate aqueous solution for 3h, and then reacted at 130°C for 18h. The generated brown precipitate was filtered and washed with deionized water for several times until the pH of the washing solution was 7. The filter cake obtained was a manganese-based material. The average valence of manganese in the manganese-based material was 3.62. The manganese-based material was ground to D using a ball mill. 90 The particle size was 3 microns, and then polymethyl acrylate: aluminum sol (20 wt% Al2O3 on a dry basis): manganese-based material: water were added in a mass ratio of 1:1:10:88, and the ball mill was continued to grind for 2 hours to obtain a manganese oxide suspension.

[0114] Impregnation with manganese oxide suspension: The cordierite substrate was impregnated in the manganese oxide suspension for 2 minutes, then dried at 80° C. for 3 hours, and calcined at 400° C. for 2 hours to obtain a solid product.

[0115] Impregnation protective agent suspension: Place zinc oxide and potassium carbonate in water at a mass ratio of 1:1 and grind them to D using a ball mill. 90 =6 microns, and a protective agent suspension with a concentration of 200 g / L is obtained. The solid product is immersed in the protective agent suspension for 2 minutes, dried at 120°C for 3 hours, and then activated: the activation temperature is 450°C; the activation time is 3 hours, and the activation gas includes 3 volume % oxygen and 97 volume % nitrogen.

[0116] The monolithic catalyst A3 is obtained. The composition and characteristics of the monolithic catalyst are shown in Table 1.

[0117] Example 4

[0118] Preparation of manganese oxide suspension: 4.17g potassium permanganate was dissolved in 40.55g deionized water, heated to 60°C and stirred to dissolve to form a potassium permanganate solution, which was mixed with 5.01g of a 50 wt% manganese sulfate aqueous solution for 3h, and then reacted at 130°C for 3h. The generated brown precipitate was filtered and washed with deionized water for several times until the pH of the washing solution was 7. The filter cake obtained was a manganese-based material. The average valence of manganese in the manganese-based material was 3.94. The manganese-based material was ground to D using a ball mill. 90 The particle size was 3 microns, and then polyvinyl alcohol (Shanghai Petrochemical): silica sol (15 wt% SiO2) on a dry basis: manganese-based material: water were added in a mass ratio of 1:1:10:88, and the ball mill was continued to grind for 2 hours to obtain a manganese oxide suspension.

[0119] Impregnation of manganese oxide suspension: The cordierite substrate was impregnated in the manganese oxide suspension for 2 minutes, then dried at 80° C. for 3 hours, and calcined at 350° C. for 2 hours to obtain a solid product.

[0120] Impregnation protective agent suspension: Place iron oxide and tetrabutyl titanate in water at a mass ratio of 1:1 and grind to D using a ball mill. 90 =5 microns, and a protective agent suspension with a concentration of 200 g / L is obtained. The solid product is immersed in the protective agent suspension for 2 minutes, dried at 120°C for 3 hours, and then activated: the activation temperature is 450°C; the activation time is 3 hours, and the activation gas includes 3 volume % oxygen and 97 volume % nitrogen.

[0121] The monolithic catalyst A4 is obtained. The composition and characteristics of the monolithic catalyst are shown in Table 1.

[0122] Example 5

[0123] The method of Example 1 is followed, except that no binder and dispersant are added to the manganese oxide suspension.

[0124] The monolithic catalyst A5 is obtained. The composition and characteristics of the monolithic catalyst are shown in Table 1.

[0125] Example 6

[0126] The method of Example 1 was followed, except that the manganese-based material was ground to D during the preparation of the manganese oxide suspension. 90 =20 microns.

[0127] The monolithic catalyst A6 is obtained. The composition and characteristics of the monolithic catalyst are shown in Table 1.

[0128] Example 7

[0129] The method of Example 1 was followed, except that the protective agent was ground to D during the preparation of the protective agent suspension. 90 =30 microns.

[0130] The monolithic catalyst A7 is obtained. The composition and characteristics of the monolithic catalyst are shown in Table 1.

[0131] Comparative Example 1

[0132] The method of Example 1 is followed, except that potassium permanganate is not added, but only manganese sulfate is added, so that the manganese oxide content in the prepared monolithic catalyst is still 22% by weight. Specifically, manganese sulfate is mixed with polyvinyl alcohol, silica sol and water to obtain a manganese-containing solution.

[0133] The monolithic catalyst D1 is obtained. The composition and characteristics of the monolithic catalyst are shown in Table 1.

[0134] Comparative Example 2

[0135] The method of Example 1 is followed, except that manganese sulfate is not added, but potassium permanganate is added, so that the manganese oxide content in the prepared monolithic catalyst is still 22% by weight. Specifically, potassium permanganate is mixed with polyvinyl alcohol, silica sol and water to obtain a manganese-containing solution.

[0136] The monolithic catalyst D2 is obtained. The composition and characteristics of the monolithic catalyst are shown in Table 1.

[0137] Comparative Example 3

[0138] The method of Example 1 was followed, except that no protective agent was added, and the solid product obtained was catalyst D3. The composition and characteristics of the monolithic catalyst are shown in Table 1.

[0139] Table 1

[0140]

[0141]

[0142] Note: The remainder in the catalyst is binder.

[0143] Test Example 1

[0144] This test example also includes a coating stability test, in which the coating stability test is measured by ultrasonic testing of the weight loss before and after 50Hz ultrasound for 30 minutes.

[0145] The monolithic catalyst prepared in the embodiment and the comparative example was placed in a fixed bed reactor, and then the refinery tail gas containing SO2, CO, and VOCs (CO concentration of 3500ppm, VOCs concentration of 300ppm, SO2 concentration of 50ppm, water vapor content of 5wt%) was introduced into the fixed bed reactor for reaction at 400°C and normal pressure. The reaction volume space velocity was 10000h -1 After the reaction starts and stabilizes for 1 hour, take samples for analysis and record the concentrations of CO and VOCs in the tail gas. The mixed gas after the reaction is passed into the tail gas absorption tank. After the test meets the environmental protection requirements, it can be further processed or vented. The test results are shown in Table 2.

[0146] Table 2

[0147]

[0148]

[0149] It can be seen from the results in Table 2 that the monolithic catalyst provided by the present invention has an excellent removal effect on carbon monoxide and volatile organic compounds.

[0150] At the same time, it can be seen from Table 2 that the integral catalyst coating of the present invention has good stability, better performance and longer service life.

[0151] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A monolithic catalyst, comprising a porous matrix, manganese oxide and a protective agent supported on the porous matrix, wherein the protective agent is selected from at least one of an acidic substance, an alkaline substance and a metal oxide; in, The average valence of manganese in the monolithic catalyst is 3.6-4.

2. The catalyst according to claim 1, wherein Based on the total weight of the monolithic catalyst, in the monolithic catalyst, the content of the porous matrix is ​​50-80% by weight, preferably 55-80% by weight; the content of manganese oxide is 10-40% by weight, preferably 15-35% by weight; the content of the protective agent is 5-35% by weight, preferably 5-30% by weight; Preferably, the manganese oxide has an α-MnO2 structure.

3. The catalyst according to claim 1 or 2, wherein The protective agent is selected from at least two of an acidic substance, an alkaline substance and a metal oxide; Further preferably, the protective agent is a metal oxide and an alkaline substance and / or an acidic substance, and the mass ratio of the metal oxide to the alkaline substance and / or the acidic substance is 1:1-8, preferably 1:1-4; Preferably, the acidic substance is selected from at least one of ethyl titanate, isopropyl titanate, tetrabutyl titanate, tetraethyl silicate, ethyl orthosilicate, methyl orthosilicate and ethyl methyl silicate, more preferably tetrabutyl titanate and / or ethyl orthosilicate; Preferably, the alkaline substance is an inorganic base, preferably at least one selected from sodium carbonate, potassium carbonate, sodium hydroxide and potassium hydroxide; Preferably, the metal oxide is zinc oxide and / or iron oxide.

4. The catalyst according to any one of claims 1 to 3, wherein The porous matrix is ​​selected from at least one of cordierite honeycomb carriers, mullite honeycomb carriers, diamond honeycomb carriers, corundum honeycomb carriers, zirconium corundum honeycomb carriers, quartz honeycomb carriers, nepheline honeycomb carriers, feldspar honeycomb carriers, alumina honeycomb carriers and metal alloy honeycomb carriers, preferably cordierite honeycomb carriers.

5. A method for preparing a monolithic catalyst, the method comprising the following steps: (1) mixing a manganese-based material with a dispersant and a binder to obtain a manganese oxide suspension, wherein the average valence of manganese in the manganese-based material is 3.6-4; (2) impregnating the porous substrate into a manganese oxide suspension and a protective agent suspension by an impregnation method, followed by drying and optionally calcining; Wherein, the protective agent is selected from at least one of an acidic substance, an alkaline substance and a metal oxide.

6. The method according to claim 5, wherein: The amounts of manganese-based material, protective agent and porous matrix are used so that in the prepared monolithic catalyst, based on the total weight of the monolithic catalyst, the content of the porous matrix is ​​50-80% by weight, preferably 55-80% by weight; the content of manganese oxide is 10-40% by weight, preferably 15-35% by weight; the content of the protective agent is 5-35% by weight, preferably 5-30% by weight.

7. The method according to claim 5, wherein: In the manganese oxide suspension, the D 90 Not more than 10 microns, preferably 1-5 microns; Preferably, the mass ratio of the manganese-based material to the dispersant and the binder on a dry basis is 1:0.05-0.7:0.05-0.8, preferably 1:0.1-0.4:0.1-0.4; Preferably, the dispersant is selected from at least one of polyvinyl alcohol, acrylic acid and methyl acrylate; Preferably, the binder is selected from at least one of silica sol, alumina sol, pseudo-boehmite and phosphate aluminum sol; Preferably, the manganese oxide suspension does not contain a surfactant.

8. The method according to any one of claims 5 to 7, wherein: The method for preparing the manganese-based material comprises the following steps: precipitating a first manganese-containing compound aqueous solution and a second manganese-containing compound aqueous solution, and then crystallizing to obtain a manganese-based material; Preferably, the precipitation conditions include: temperature of 30-90°C and time of 0.3-3h; Preferably, the crystallization conditions include: temperature of 100-150°C and time of 1-20h; Preferably, the first manganese-containing compound is potassium permanganate and / or sodium permanganate; Preferably, the concentration of the first manganese-containing compound aqueous solution is 2-15 wt %; Preferably, the second manganese-containing compound is at least one of manganese sulfate, manganese nitrate and manganese acetate; Preferably, the concentration of the second manganese compound-containing aqueous solution is 30-70 wt %.

9. The method according to any one of claims 5 to 8, wherein: The impregnation method in step (2) comprises: contacting the porous substrate with a manganese oxide suspension, and then drying and calcining to obtain a solid product; contacting the solid product with a protective agent suspension, and then drying; Preferably, the calcination conditions include: a temperature of 300-500° C. and a time of 1-5 h.

10. The method according to any one of claims 5 to 9, wherein: The protective agent is selected from at least two of an acidic substance, an alkaline substance and a metal oxide; Further preferably, the protective agent is a metal oxide and an alkaline substance and / or an acidic substance, and the mass ratio of the metal oxide to the alkaline substance and / or the acidic substance is 1:1-8, preferably 1:1-4; Preferably, the acidic substance is selected from at least one of ethyl titanate, isopropyl titanate, tetrabutyl titanate, tetraethyl silicate, ethyl orthosilicate, methyl orthosilicate and ethyl methyl silicate, more preferably tetrabutyl titanate and / or ethyl orthosilicate; Preferably, the alkaline substance is an inorganic base, preferably at least one selected from sodium carbonate, potassium carbonate, sodium hydroxide and potassium hydroxide; Preferably, the metal oxide is zinc oxide and / or iron oxide; Preferably, in the protective agent suspension, the protective agent has a D 90 Not more than 10 microns, preferably 1-10 microns; Preferably, the concentration of the protective agent suspension is 50-250 g / L; Preferably, the porous matrix is ​​selected from at least one of cordierite honeycomb carrier, mullite honeycomb carrier, diamond honeycomb carrier, corundum honeycomb carrier, zirconium corundum honeycomb carrier, quartz honeycomb carrier, nepheline honeycomb carrier, feldspar honeycomb carrier, alumina honeycomb carrier and metal alloy honeycomb carrier, preferably cordierite honeycomb carrier.

11. The method according to claim 9, wherein: The method further comprises: activating the material obtained in step (2) to obtain a monolithic catalyst; Preferably, the activation conditions include: an activation temperature of 50-350°C, preferably 100-300°C; an activation time of 0.5-5 hours, preferably 0.8-3 hours; Preferably, the activation is carried out in the presence of an activation gas, the activation gas comprises oxygen and an inert gas, and the volume content of the inert gas in the activation gas is 1-50%, preferably 2-30%.

12. Use of the monolithic catalyst described in any one of claims 1 to 4 or the monolithic catalyst prepared by the preparation method described in any one of claims 5 to 11 in waste gas treatment, preferably in the coordinated purification of carbon monoxide and volatile organic compounds, more preferably in the coordinated purification of carbon monoxide and volatile organic compounds in at least one of refinery exhaust gas, power plant exhaust gas, steel mill exhaust gas, flue gas generated by urban waste incineration and motor vehicle exhaust gas.

13. A method for synergistically purifying carbon monoxide and volatile organic compounds, the method comprising: contacting the tail gas containing carbon monoxide and volatile organic matter with the monolithic catalyst; Wherein, the monolithic catalyst is the monolithic catalyst described in any one of claims 1 to 4 or the monolithic catalyst prepared by the preparation method described in any one of claims 5 to 11; Preferably, the contacting conditions include: a temperature of 20-500°C, preferably 100-400°C; Volume space velocity is 500-100000h -1 , preferably 2000-20000h -1 ; Preferably, the carbon monoxide content in the tail gas is 0.1-5000ppm; Preferably, the content of volatile organic matter in the tail gas is 10-300 ppm; Preferably, the exhaust gas includes at least one of refinery exhaust gas, power plant exhaust gas, steel mill exhaust gas, flue gas generated by urban waste incineration and motor vehicle exhaust gas.

Citation Information

Patent Citations

  • Preparation method of Pt-BaTiO3 nano-catalyst for CO catalytic oxidation

    CN103263917A

  • Preparation method for AuAg@SiO2 nanometer catalyst of catalytic oxidation CO

    CN107519871A

  • Manganese oxide catalyst, integral catalyst containing manganese oxide and application thereof

    CN107519860A

  • Preparation method of catalyst for catalytic purification of volatile organic compounds (VOC) by microwave electrodeless light

    CN109865518A

  • Preparation method of catalyst for removal of oxygen-containing volatile organic compounds

    CN110586078A